Structural school characteristics and neighborhood risk factors: Associations with student-reported school climate in a large, urban public school district in the United States - Moore, Stephanie A.; Ouellette, Rachel R.; Connors, Elizabeth H. (Frontiers in Education, 2023)
School climate consistently predicts youth academic success, social-emotional well-being, and substance use, and positive school climate can buffer the negative effects of community violence exposure on youth development. Various structural school and neighborhood factors have been associated with school climate, but prior research has not examined these relations comprehensively. We examined the relation between 18 school building and school neighborhood factors with student-reported school climate among 15,833 students in 124 public schools in a large, urban district in the United States. In this sample, attendance rate was most consistently associated with school climate (β = 0.015; p < .001). Teacher years of experience, mobility rate, number of students in special education, adult arrests in the school neighborhood, and service calls for shootings and dirty streets and alleys in the school neighborhood were also significantly associated with various domains of school climate. These findings highlight the need for future longitudinal research on the influence of both school building and school neighborhood factors on school climate for public schools. Schools in our sample had a wide range of school climate scores despite consistently high crime rates and other structural risk factors such as low socioeconomic status throughout the city, so there are implications for researchers and education leaders to work together to identify opportunities for schools to foster positive school climate despite systemic school and/or neighborhood risk factors.